2021
DOI: 10.5867/medwave.2021.01.8114
|View full text |Cite
|
Sign up to set email alerts
|

Offloader knee braces for knee osteoarthritis

Abstract: INTRODUCTION Knee osteoarthritis is a relevant health problem given its high prevalence and associated disability. Within the non-pharmacological management alternatives, the use of offloader knee braces has been proposed, however, there is no consensus in the literature regarding its indication. METHODS We searched in Epistemonikos, the largest database of systematic reviews in health, which is maintained by screening multiple information sources, including MEDLINE, EMBASE, Cochrane, among others. We extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It should be noted that in people with OA, less extension occurs in the late stages of stance in the knee, which is associated with a delay in the peak angle of flexion in the swing phase [18,36]. As in Sharma's study [37], the change of knee flexion angle during gait has been introduced as a factor determining the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that in people with OA, less extension occurs in the late stages of stance in the knee, which is associated with a delay in the peak angle of flexion in the swing phase [18,36]. As in Sharma's study [37], the change of knee flexion angle during gait has been introduced as a factor determining the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the piston forces created by the brace on the patient's limb during gait and different places of the brace on the knee, during successive wearing and removal, which, for 5 mm of wrong placement of the brace joint on the limb, can cause major changes in limb mechanics [17]. Thus, it seems that the incompatibility of brace and knee joint motion, inconsistency between brace knee joint with the anterior-posterior movement of the femur over tibia during knee flexion, brace piston movement on the limb, and application of continuous corrective force by stretching on the knee in all gait stages are factors that braces are not accepted by patients [12,18]. These tips led us to the design of the new knee joint.…”
Section: English Versionmentioning
confidence: 99%
“…et al, 2021). This brace focused on load distribution away from the affected compartment and correcting the knee alignment to reduce pain, enhance the quality of life, and delay disease progression (McGibbon et al, 2021, Moller et al, 2021. It was suggested that the knee brace could decrease the force over the knee compartment between 5.5% and 30%, which helps in OA progression and soft tissue repairs (McGibbon et al, 2021, Deie et al, 2013.…”
Section: Conservative Interventionsmentioning
confidence: 99%
“…Moreover, some patients complained of a heavy feeling of the brace or slipping down feeling or anxiety with using the knee brace (Schmalz et al, 2010, Thoumie et al, 2018, van Egmond, 2017. Hence, here are some tips to consider before using the knee brace: (a) the knee brace is more recommended for patients with body mass less than 30 kg/m 2 and with a low Kellgren-Lawrence scale, (b) it is recommended for relatively young patients, (c) it is recommended to be worn for at least six months for better outcomes, (d) and it is recommended to choose the right size (Moller et al, 2021, Draper et al, 2000. In summary, using a knee brace is associated with biomechanical benefits, clinical benefits, and quality of life benefits.…”
Section: Conservative Interventionsmentioning
confidence: 99%